In silico analysis of 16S ribosomal RNA gene sequencing-based methods for identification of medically important anaerobic bacteria. Issue 5 (17th October 2006) - Woo, Patrick C Y; Chung, Liliane M W; Teng, Jade L L; Tse, Herman; Pang, Sherby S Y; Lau, Veronica Y T; Wong, Vanessa W K; Kam, Kwok-ling; Lau, Susanna K P; Yuen, Kwok-Yung
Abstract : This study is the first study that provides useful guidelines to clinical microbiologists and technicians on the usefulness of full 16S rRNA sequencing, 5′-end 527-bp 16S rRNA sequencing and the existing MicroSeq full and 500 16S rDNA bacterial identification system (MicroSeq, Perkin-Elmer Applied Biosystems Division, Foster City, California, USA) databases for the identification of all existing medically important anaerobic bacteria. Full and 527-bp 16S rRNA sequencing are able to identify 52–63% of 130 Gram-positive anaerobic rods, 72–73% of 86 Gram-negative anaerobic rods and 78% of 23 anaerobic cocci. The existing MicroSeq databases are able to identify only 19–25% of 130 Gram-positive anaerobic rods, 38% of 86 Gram-negative anaerobic rods and 39% of 23 anaerobic cocci. These represent only 45–46% of those that should be confidently identified by full and 527-bp 16S rRNA sequencing. To improve the usefulness of MicroSeq, bacterial species that should be confidently identified by full and/or 527-bp 16S rRNA sequencing but not included in the existing MicroSeq databases should be included.